Emotional priming of digital images through mobile telesmell and virtual food. (1st January 2016) - Braun, Marius Hans; Pradana, Gilang Andi; Buchanan, George; Cheok, Adrian David; Velasco, Carlos; Spence, Charles; Aduriz, Andoni Luis; Gross, Jade; Lasa, Dani
The sense of smell has been recognized as an important factor governing our emotions and memory. Nevertheless, it remains the most underexplored sense and is still a relatively new modality in the domain of Human–Computer Interaction. In this article, we report on initial findings from our ongoing research to find support for the significance of smell next to and above other senses as a medium of digital communication. Firstly, we examine the effect of olfactory cues on the emotional perception of digital images on mobile devices with a hardware tele-smell device, Scentee. The preliminary results reveal that the addition of scent significantly modulated the emotional perception of the images, with the effect especially noticeable when scents had a contrasting emotional valence to the image content. We also introduce the application of Scentee as a virtual multi-sensory dining experience aimed at sharing the experience or preparing dishes and scents more publicly.